Biochemical and Clinical Features of Insulinoma in a Patient with Turner Syndrome - Darius A. Schneider; M. Zare; F. Behnia; M. Matesan; T. Tylee (Case Reports in Endocrinology)
Turner syndrome (TS), i.e., mosaic or nonmosaic states with only one normal X chromosome in females, is characterized by a wide spectrum of somatic, hormonal, and metabolic features. Here we report an unusual case of recurrent hypoglycemia in a 53-year-old woman with TS. Biochemical work-up following a 72h fast revealed detectable, inappropriate for low glucose insulin levels and elevated proinsulin and beta-hydroxybutyrate (BOHB) levels. MR and multiphase CT showed a solid 2.5 cm pancreatic tail mass with absent uptake in the 111In-pentetreotide (Octreoscan) scan. Subsequent hepatic vein blood sampling after intra-arterial calcium stimulation showed sharp increase in insulin and modest increase in proinsulin levels. The patient underwent excision of the mass with resolution of symptoms. Histopathologic examination confirmed the neuroendocrine etiology of the tumor. This is, to our knowledge, the third report of TS and concomitant insulinoma. Impaired counterregulatory response to hypoglycemia in patients with TS may result in symptomatic hypoglycemia with only mild insulin elevation and elevated proinsulin in setting of hypoglycemia may be the only indication of insulinoma in these patients. BOHB levels should not be used for ruling out EHH in patients with TS.